Embodying two shores of the Mediterranean Sea: the liminal masculinity of minors migrating alone to Spain - Alonso, Bakea; Longo, Valentina; Ruiz Garriga, Álvaro (Frontiers in Sociology, 2024)
The article aims to provide an analysis based on the practical experience of social intervention in violence prevention with migrant minors arriving alone in Spain. In order to offer keys and recommendations, and based on situated knowledge, we provide insights on how to approach the intervention framework from a methodological point of view using liminal spaces as border and transition places that need to be named and taken into consideration for a transformative work. Different metaphorical borders, characterized by tension and potential change, are analyzed from a gender and intersectional perspective. We discuss the Law-border and the tension between protection they receive as minors and exclusion/politics of suspicion they receive as migrants. The Age-border (children/men) is discussed taking into account the different gender regimes they cross. The Color-border: here issues of racism and colonialism are considered. Finally, we discuss the Masculinity-border and the tension between reception and the reproduction of violence. We use the concept of liminal masculinities as a specific state or form that subordinate or marginalized masculinity adopts in migrant minors, suspended legally, functionally, and biographically, among others borders.